Photocatalytic water splitting for hydrogen production using carbon nanotubes-based catalysts under visible light - Koh, Wing Hong. (2010)
The most common methods that are widely used to produce hydrogen are steam reforming and catalytic reforming. Both methods rely on the use of fossil fuels, thus generating large amounts of greenhouse gases such as carbon dioxide. Hydrogen production from photocatalytic water splitting using solar energy and photocatalysts is considered as one of the promising routes. In the experiments involved in this Final Year Project, water splitting photocatalysts have been successfully synthesized using multi-walled carbon nanotubes (MWNT) as support. MWNT was useful as a support as it is able to serve as an electrical conductor and is corrosion resistant. Its electrical conductivity allows for the transfer of electrons from the conduction band of CNTs to metal particles deposited on the surface of MWNTs, while photo-generated valence band holes remain on MWNT. This enables efficient separation and stronger photocatalytic reactions by greatly reducing the possibility of electron-hole recombination. Being corrosion resistant allows MWNT-supported catalysts to last longer when used to catalyse reactions. Various parameters such as metal loading, pH and cooling time have been tested to investigate the effect on the activity of the photocatalysts synthesized. Experiments using single-walled carbon nanotubes (SWNT) and carbon nanospheres (CNS) as photocatalyst supports were conducted to test their effectiveness. An extended water-splitting test was then conducted using the optimal photocatalysts and experimental conditions to test the stability of the catalytic reaction. The best H2 production rate obtained was 465.97 μmol/h.